2007
DOI: 10.1200/jco.2006.09.1900
|View full text |Cite
|
Sign up to set email alerts
|

How Often Do BRCA Mutation Carriers Tell Their Young Children of the Family's Risk for Cancer? A Study of Parental Disclosure of BRCA Mutations to Minors and Young Adults

Abstract: Children of BRCA mutation carriers learn of their parents genetic test results many years before preventive interventions are indicated. Further research is needed to examine how young individuals understand this information and its psychosocial impact and influence on subsequent lifestyle and health behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
110
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 26 publications
7
110
1
1
Order By: Relevance
“…The incidences observed are in line with those previously reported in either cross-sectional or shorter-term follow-up studies. [20][21][22][23][24][25]27 These studies have also reported, similar to this study, more positive than negative family relationship effects. [20][21][22]24,27 Taken together, these results offer reassurance about potential family effects to individuals considering BRCA1/2 testing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidences observed are in line with those previously reported in either cross-sectional or shorter-term follow-up studies. [20][21][22][23][24][25]27 These studies have also reported, similar to this study, more positive than negative family relationship effects. [20][21][22]24,27 Taken together, these results offer reassurance about potential family effects to individuals considering BRCA1/2 testing.…”
Section: Discussionsupporting
confidence: 89%
“…Although positive family relationship effects have been reported more frequently than negative ones, these results come mainly from cross-sectional studies with small samples and with a time since result disclosure, which varied considerably between subjects. [20][21][22][23][24][25] Only a few studies were specifically conducted to quantify the effects of the genetic testing process on family relationships. [26][27][28] Data on the incidence of long term (i.e., >1 year) of family relationship effects after the receipt of test result are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This gender difference in disclosures might extend to offspring, as daughters were found more likely to be told than sons in some studies (Blandy et al, 2003;Patenaude et al, 2006;MacDonald et al, 2007). A similar trend may be seen in more extended relatives (Claes et al, 2003).Regarding disclosures to offspring, Bradbury et al (2007) noted that the majority of adult and late adolescent children were told about their parent's mutation or the hereditary risk of cancer. Parents were less likely to disclose this information to younger children (Patenaude et al, 2006;Bradbury et al, 2007).…”
mentioning
confidence: 90%
“…Some tellers were able to overcome their concerns and fulfill the duty they felt to inform their family members, often by clinging to the hope of scientific progress (Hallowell et al, 2003). Others felt that the potential for disturbing or upsetting their relatives outweighed the benefits of disclosing, at least for the time being (Hallowell, 1999;Bradbury et al, 2007;Hallowell et al, 2005a;Hughes et al, 2002).Other less commonly mentioned barriers or deterrents for disclosures to family members included geographic distance Green et al, 1997), the assumption other relatives would disclose the information to family members (Claes et al, 2003), dilemmas 16 between family members about how to best disclose to others (Hallowell et al, 2005a), the teller's lack of confidence in their own communication skills (Daly et al, 2001;, the fear that the information would be misunderstood by family members (Hughes et al, 2002;Hamilton et al, 2005) and thinking the information would not be useful to the family member (Forrest et al, 2003;MacDonald et al, 2007;Daly et al, 2001;Claes et al, 2003). …”
mentioning
confidence: 99%
“…However, the majority of the respondents who tested positive but did not share their results with their children had indicated that providing their children with information was a motivation for them to be tested, and so it is likely they will pass on this information when the children are older. Previous studies on families with inherited breast and ovarian cancers showed that the majority of parents (70-80%) discussed their genetic result with children of adult age, regardless of their carrier status 27,28 and the age of the children was positively associated with communication. Most parents who did not disclose their result did so because they thought their children were too young or immature.…”
Section: Discussionmentioning
confidence: 96%